Strategi Komunikasi Dalam Interaksi Dengan Mahasiswa Pertukaran Asing - Nabilla Kusuma Vardhani; Agnes Siwi Purwaning Tyas (Jurnal Gama Societa, 2018)
A communication process can be considered success when the communicant receives and understand the message as what the communicators meant. This effective communication will result in the achievement of a communication goal. However, the effective communication might be difficult to happen when both interlocutors do not have the same native language. It happens because the language barriers may influence the process of understanding the message while the communication happens. To overcome the problem, the communicator applies some communication strategies. This comparative study used observations and interviews to examine the communication strategies used by first- and third-year English students of Universitas Gadjah Mada Indonesia during spoken interactions in English with exchange students from Cheng Du Textile College China. The objective of this study is to observe how the first- and third- year study overcome their communication problem while talking with non-English native speaker students and use the data as inputs to develop the next curriculum. The writer uses Tarone’s communicative strategies to identify the students’ strategies. The result shows that ‘Literal Translation’ is not used by English students while communicating with exchange students, ‘Circumlocution’ and ‘Message Abandonment’ are only used by third year students, ‘Appeal for Assistance’ and ‘Topic Avoidance’ are only used by first year students, third year students’ most used strategies are ‘Mime’ and ‘Word Coinage’, and first year students’ most used strategies are ‘Approximation’ and ‘Mime’.